Application of the advection-dispersion equation to characterize the hydrodynamic regime in a submerged packed bed reactor - Albuquerque, António (2004)
The hydraulic characteristics of a laboratory submerged packed bed, filled with a volcanic stone, pozzuolana, have been experimentally investigated through tracer tests. Sets of essays at flow rates from 1 to 2.5 l/h in clean conditions were performed. The results showed a considerable amount of dispersion through the filter as the hydraulic loading was changed, indicating a multiplicity of hydrodynamic states, approaching its behavior to plug flow. An analytical solution for the advection-dispersion equation model have been developed for a semi-infinite system and we have considered an appropriate physical boundary condition. A numerical simulation using finite difference schemes is done taking into account this particular boundary condition that changes according to the flow rates. Proper formulation of boundary conditions for analysis of column displacements experiments in the laboratory is critically important to the interpretation of observed data, as well as for subsequent extrapolation of the experimental results to transport problems in the field.